Interactive Network Platform Improves Compliance and Efficacy of Subcutaneous Immunotherapy for Patients with Allergic Rhinitis - Shen, Zhiying (Patient Prefer Adherence, 2019)
BACKGROUND: Allergic rhinitis (AR) is a common chronic inflammatory disease of nasal mucosa worldwide, and its symptoms seriously affect the lives of patients. Subcutaneous immunotherapy (SCIT) is an effective treatment for AR, but it is also associated with low patient compliance and difficulties in fully achieving therapeutic effects. OBJECTIVE: In this prospective randomized controlled study, we verified the effects of an interactive network platform named “U breath” in improving patient compliance and the efficacy of SCIT in patients with AR. METHODS: A total of 148 patients who received SCIT were recruited as participants and randomly assigned to either the standardized management (SM) or the interactive network platform management (INP) group. The SM group experienced the standard management SCIT process. The INP group experienced a new management approach based on an interactive network platform called “U breath”. The compliance rate, combined symptom and medication score (CSMS), visual analogue scale score and the rhinoconjunctivitis quality of life questionnaire (RQLQ) results were evaluated at baseline and 1-year postintervention for the two groups. RESULTS: Within the first year of treatment, the INP group had a higher compliance rate than did the SM group, with a statistically significant difference (P<0.05). The INP group showed better clinical improvement than the SM group did in terms of the VAS score, and the RQLQ score except the sleep problems (P< 0.05). CONCLUSION: This study confirmed that the application of an interactive network platform is of great significance for improving patient compliance and the treatment effects of SCIT in patients with AR.